Mapping registered nurse anaesthetists' intraoperative work: tasks, multitasking, interruptions and their causes, and interactions: a prospective observational study - Olin Karolina; Göras Camilla; Nilsson Ulrica; Unbeck Maria; Ehrenberg Anna; Pukk-Härenstam Karin; Ekstedt Mirjam (BMJ PUBLISHING GROUP, 2022)
Introduction
Safe anaesthesia care is a fundamental part of healthcare. In a previous study, registered nurse anaesthetists (RNAs) had the highest task frequency, with the largest amount of multitasking and interruptions among all professionals working in a surgical team. There is a lack of knowledge on how these factors are distributed during the intraoperative anaesthesia care process, and what implications they might have on safety and quality of care.
Objective
To map the RNAs' work as done in practice, including tasks, multitasking, interruptions and their causes, and interactions, during all phases of the intraoperative anaesthesia work process.
Methods
Structured observations of RNAs (n=8) conducted during 30 procedures lasting a total of 73 hours in an operating department at a county hospital in Sweden, using the Work Observation Method By Activity Timing tool.
Results
High task intensity and multitasking were revealed during preparation for anaesthesia induction (79 tasks/hour, 61.9% of task time spent multitasking), anaesthesia induction (98 tasks/hour, 50.7%) and preparation for anaesthesia maintenance (86 tasks/hour, 80.2%). Frequent interruptions took place during preoperative preparation (4.7 /hour), anaesthesia induction (6.2 /hour) and preparation for anaesthesia maintenance (4.3 /hour). The interruptions were most often related to medication care (n=54, 19.8%), equipment issues (n=40, 14.7%) or the procedure itself (n=39, 14.3%). RNAs' work was conducted mostly independently (58.4%), but RNAs interacted with multiple professionals in and outside the operating room during anaesthesia.
Conclusion
The tasks, multitasking, interruptions and their causes, and interactions during different phases illustrated the RNAs' work as done, as part of a complex adaptive system. Management of safety in the most intense phases-preparing for anaesthesia induction, induction and preparing for anaesthesia maintenance-should be investigated further. The complexity and adaptivity of the nature of RNAs' work should be taken into consideration in future management, development, research and education.